2017
DOI: 10.1080/01443615.2017.1346594
|View full text |Cite
|
Sign up to set email alerts
|

Outpatient cervical ripening in a district general hospital: a five-year retrospective cohort study

Abstract: The number of women undergoing induction of labour has risen steadily in recent years. Outpatient induction is becoming more common in the UK in response to the required increase in resources, although evidence supporting its safety is lacking. We reviewed the notes of low-risk women presenting for outpatient cervical ripening using prostaglandins over a five-year period, and compared our neonatal and maternal outcomes to local and national data. Of the 502 eligible women, 400 underwent outpatient treatment. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…As a result of the worldwide increasing number of women undergoing IOL and related resource and space burden at the delivery units, outpatient inductions have been adopted in some countries. As the phase of cervical ripening is relevant for outpatient as well as inpatient management, our results on time from admission to start of active labor in this national cohort is of value in spite of the related limitations . Our definition of start of active labor may limit the generalizability of the present study.…”
Section: Discussionmentioning
confidence: 86%
“…As a result of the worldwide increasing number of women undergoing IOL and related resource and space burden at the delivery units, outpatient inductions have been adopted in some countries. As the phase of cervical ripening is relevant for outpatient as well as inpatient management, our results on time from admission to start of active labor in this national cohort is of value in spite of the related limitations . Our definition of start of active labor may limit the generalizability of the present study.…”
Section: Discussionmentioning
confidence: 86%
“…Outpatient cervical ripening has already been adopted in other countries outside of the United States. [4][5][6][7] Routinely, women with an unfavorable cervix undergo cervical ripening prior to an induction of labor. 2,8 Cervical ripening is often a lengthy process equating to a considerable amount of time spent in the hospital preparing the cervix for medical induction of labor.…”
mentioning
confidence: 99%
“…Biem et al 8 reported that women in the outpatient setting had an overall higher satisfaction rate. Evidence for women's preference in outpatient IOL is supported by the literature, and satisfaction is generally higher in the outpatient population 17,45–48 . Induction of labor may interfere with women's ability to express a personal choice or feel in control of their birth experience 44 .…”
Section: Discussionmentioning
confidence: 95%
“…Having an empowering birth experience is not necessarily about the type of labor or birth; moreover, it includes the woman's decision‐making power and her involvement in the decision‐making process 24 . Providing women with an outpatient option when requiring cervical ripening potentially improves the decision‐making process, sense of control and her overall experience with the IOL 44,47,48 …”
Section: Discussionmentioning
confidence: 99%